Why do liver transplant patients so often become obese? The addiction transfer hypothesis. Issue 1 (July 2015) - Brunault, Paul; Salamé, Ephrem; Jaafari, Nematollah; Courtois, Robert; Réveillère, Christian; Silvain, Christine; Benyamina, Amine; Blecha, Lisa; Belin, David; Ballon, Nicolas
Abstract In patients who receive transplantation for alcohol liver disease, obesity and metabolic syndrome are highly prevalent after transplantation and both contribute to a significant proportion of cardiovascular complications, late morbidity and mortality in this population. Although immunosuppressive medications have been hypothesised to explain some of these post-liver transplantation (LT) metabolic complications, they cannot be considered the sole cause of obesity and metabolic syndrome, and the high prevalence of these illnesses remains unexplained. Given the significant overlap between the neurobiological, psychiatric and psychological factors that underlie alcohol addiction and reward-related behavioural dyscontrol disorders such as food addiction (FA), we hypothesised that the high prevalence of obesity and metabolic syndrome reported in patients who receive transplantation for alcohol liver disease could be explained at least partially by a switch in some individuals from a previous alcohol addiction to post-transplantation FA (i.e., addiction transfer = addiction switch). In our integrative model, we also speculate that an increased prevalence of FA or alcohol addiction may occur in patients with both specific psychobiological profiles and shared risk factors. We further hypothesise that in the subpopulation of patients who develop either alcohol addiction or FA after LT, those with high insight with regard to the consequences of alcohol use could be at higher risk for FA, whereas those with low insight could be at higher risk for alcohol addiction. We discuss here evidence for and against this hypothesis and discuss which patients could be more vulnerable to these two addictions after LT. Because it will not be either possible or ethical to test some of our hypotheses in humans, future studies should test these hypotheses using a translational strategy, using both clinical and preclinical approaches. If our hypotheses could account for the significant increase in obesity and metabolic syndrome after LT, this would lead to new avenues for research and preventive as well as therapeutic interventions for alcohol-related LT patients. All patients with previous or current alcohol addiction should be systematically screened for FA and followed up for subsequent risk of obesity and metabolic syndrome. Such strategies might be effective in improving survival, outcomes and quality of life after LT and also in the overall population of patients with alcohol addiction. By determining common risk factors for both alcohol addiction and FA using a translational approach, our model could help to find novel psychopharmacological and psychological strategies that might be effective in both FA and alcohol addiction.